2011
DOI: 10.1038/mp.2011.23
|View full text |Cite
|
Sign up to set email alerts
|

Discovering imaging endophenotypes for major depression

Abstract: Psychiatry research lacks an in-depth understanding of mood disorders phenotypes, leading to limited success of genetics studies of major depressive disorder (MDD). The dramatic progress in safe and affordable magnetic resonance-based imaging methods has the potential to identify subtle abnormalities of neural structures, connectivity and function in mood disordered subjects. This review paper presents strategies to improve the phenotypic definition of MDD by proposing imaging endophenotypes derived from magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
202
2
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 260 publications
(216 citation statements)
references
References 164 publications
(199 reference statements)
9
202
2
3
Order By: Relevance
“…These authors suggested that, given the role of the caudate nucleus in reward processing (Yacubian et al, 2006), this connectivity pattern may be related to anhedonia in depression. While these inconsistent results may simply be due to the use of different methods of analysis (Hasler and Northoff, 2011), they could also be linked to different stages of the depressive illness (e.g. strengthened vs. decoupled links between emotion, cognition and bodily sensations), whereby early (or first onset) and recurrent (or chronically) depressed individuals may show different connectivity patterns.…”
Section: 1mentioning
confidence: 99%
See 3 more Smart Citations
“…These authors suggested that, given the role of the caudate nucleus in reward processing (Yacubian et al, 2006), this connectivity pattern may be related to anhedonia in depression. While these inconsistent results may simply be due to the use of different methods of analysis (Hasler and Northoff, 2011), they could also be linked to different stages of the depressive illness (e.g. strengthened vs. decoupled links between emotion, cognition and bodily sensations), whereby early (or first onset) and recurrent (or chronically) depressed individuals may show different connectivity patterns.…”
Section: 1mentioning
confidence: 99%
“…Unfortunately no studies have investigated this issue in depressed patients thus far, but it has been proposed that the divergence between structural and functional connectivity might be strong in mood disorders, perhaps mediated by neurochemical imbalance (Hasler and Northoff, 2011 Ochsner et al, 2004), recent studies have investigated how these regions respond to emotional stimuli in depression, and specifically whether rest-to-task transition in emotional contexts is affected by TN-persistence and TP-deficiency ( Figure 4). …”
Section: 1mentioning
confidence: 99%
See 2 more Smart Citations
“…Neuronska mreža mirovanja je jedna od tri velike neuralne mreže za koje se pretpostavlja da međusobnim delovanjem u velikoj meri učestvuju u obradi informacija tokom emocionalnih i kognitivnih procesa (Chen et al, 2013). Nekoliko teorijskih modela ponudilo je objašnjenje za povezanost različitih aspekata aktuelne depresivne epizode i disfunkcija neuronske mreže mirovanja (Hasler & Northoff, 2011;Marchetti et al, 2012;Whitfield-Gabrieli & Ford, 2012). Psihološki procesi poput autobiografskih sećanja, projekcije u budućnost, i misli o sebi se dovode u vezu sa aktivnošću ove mreže, te se smatra da ona odslikava unutrašnji fokus osobe (Christoff, Cosmelli, Legrand, & Thompson, 2011;Fossati et al, 2003;Ochsner, Bunge, Gross, & Gabrieli., 2002).…”
unclassified